An interesting case of neurocutaneous syndrome - Kedlaya, Shraddha K.; Palanisamy, Lenin Sankar; Veeramani, Ravikumar; Ramachandran, M. (International Journal of Research in Medical Sciences, 2023)
Neuroichthyosis is a group of rare genetically determined disease with cutaneous and neurological manifestations due to abnormalities in any of the following: lipid metabolism, glycoprotein synthesis, or intracellular vesicle trafficking. There are about 16 disorders with known genetic aetiology like Sjogren Larssons syndrome (SLS), Refsum disease, Gauchers disease type 2, ELOVL4 deficiency etc. Among the various neuroicthyosis syndromes, Sjogren Larsson syndrome is the most common entity characterised by ichthyosis, spastic diplegia or tetraplegia, cognitive dysfunction, seizures, and a maculopathy with glistening white dots. We hereby report a case of neuroichthyosis disease who presented to us with developmental delay, spastic paraplegia, seizure and ichthyosis, whose genetic testing showed homozygous mutation in ALDH3A2, suggestive of Sjogren Larsson syndrome.